ナンキョク ショウワ キチ デノ チョウ コウセイノウ ジシン ケイ ニ ヨル カンソク - 長坂, 健一; ナガサカ, ケンイチ; 神沼, 克伊; カミヌマ, カツタダ; 渋谷, 和雄; シブヤ, カズオ; Nagasaka, Ken-ichi; Kaminuma, Katsutada; Shibuya, Kazuo (1991)
P(論文) 南極・昭和基地(69.005°S 39.582°E)では, グローバル地震観測網のPOSEIDON計画の一環として, 1989年(JARE-30)に広帯域フィードバック型地震計STS (Streckeisen seismometer)が設置された。1990年(JARE-31)には, 前年度にみられた問題点に対して改良を加えるとともに, 引き続いてSTSによる地震観測を行い, いくつかの良好な記録を得ることができた。1990年5月からは, 定常的にディジタル記録の収録も開始された。ディジタル記録の日本への送信テストも実施され, 必要なときには昭和基地の地震記象がすぐにでも入手可能になった。しかし, なおSTSによる地震観測は性善されるべき問題点も多く, 温度変化に対する対策の必要がある。 A three-component broadband STS (Streckeisen seismometer) seismograph was installed at Syowa Station in 1989,to obtain precise (digital) seismic record for the study of the earth's interior and earthquakes. The STS observation system at Syowa Station is introduced and some examples of digital seismogram are shown in this paper. The STS system has two different outputs, BRB (Broad-Band : 0.1∿20s/0.1∿360s) and LP (Long-Period : longer than 20s), with a dynamic range of at least 120dB. Seismic signals are recorded in digital form together with analog seismogram for monitoring. The BRB output is currently recorded with a longterm thermal pen recorder and the digital recording system by use of personal computers, while the LP output is recorded with the pen recorder and the cassette logger. Well recorded events, most of these are large events, are compiled into floppy disks from the digital recording system approximately once a week. The digital records were transmitted successfully to National Institute of Polar Research, Japan via the satellite telecommunications system. departmental bulletin paper